Pengaruh Bauran Komunikasi Pemasaran Terhadap Keputusan Pembelian (Studi Kasus pada Produk Mie Instant Indofood Semarang) - Latief, Muhammad Chaerul (Universitas Semarang, 2009)
The aim of the research to know the influence of the integrated communicationmarketing toward the decision of purchasing lndofood instant noodles product either partial or simultant. This research used survey method and the analysis tool Double Regression. It is concluded that, as a partial, there are four of five independent variables which have a significant influence toward the decision of consumer purchasing Indofood noodles instant product. These are advertising, personal selling, sales promotion and public relation. Direct marketing doesn't have a significant influence toward the decision of purchasing lndofood noodles instant product. Simultaneously, independent, variable has a significant influence toward the decision of a noodles instant product.